Experimental and fractal studies on corrosion inhibition performance of Ophiopogon japonicus leaf extract on carbon steel in HCl. (13th September 2019) - Wang, Qihui; Wang, Yali; He, Miao; Ni, Zihui; Wang, Qianyu; Bao, Hebin; Li, Xueming; Yang, Wenjing; Tao, Xiongxin
Abstract: In this work, the performance and inhibition mechanism of Ophiopogon japonicus leaf extract as corrosion inhibitor of carbon steel in HCl solution were systematically investigated. Electrochemical test results show that Ophiopogon japonicus leaf extract, as a mixed—type corrosion inhibitor, could effectively inhibit the corrosion of carbon steel in HCl solution. The adsorption mechanism of the Ophiopogon japonicus leaf extract on the surface of carbon steel can be represented by the Langmuir adsorption isotherm. Besides, the inhibitors showed good inhibitory activity in a broad range of temperatures. The fractal dimension of corrosion morphology of carbon steel indicates that there are significant differences in the fractal dimension of corrosion morphology under different corrosion conditions. This work provides a useful reference for the fractal theory in evaluating the inhibition performance of plant extracts.